Determining Corporate Mens Rea through Strict Liability and Vicarious Liability in Corporate Crimes - Halilintar Cakra Negara; Rahaldy Briwijaya (Fakultas Hukum Universitas Janabadra, 2026)
This study examines how corporate mens rea can be determined through strict liability and vicarious liability within the context of modern corporate criminal responsibility, with a particular focus on the Indonesian legal system. The research adopts a normative juridical approach, combining conceptual analysis, statutory interpretation, and examination of judicial practice, including the application of PERMA No. 13/2016 and KUHP 2023. The findings show that strict liability constructs corporate mens rea by presuming fault from harmful outcomes or regulatory violations, making it suitable for public-welfare and high-risk regulatory offenses. Meanwhile, vicarious liability attributes the mental state of corporate agents to the corporation, enabling the prosecution of intentional offenses such as corruption, fraud, and financial crime. Indonesia applies both doctrines but in a fragmented and inconsistent manner across sectoral statutes. The absence of harmonization, limited investigative capacity, unclear evidentiary standards for structural fault, and lack of compliance-based defenses undermine effective enforcement. This study concludes that strict liability and vicarious liability should function as complementary mechanisms for establishing corporate mens rea, and that Indonesia requires a more coherent, integrated framework to enhance accountability and align with global developments in corporate criminal law.